2004
DOI: 10.1002/eji.200425223
|View full text |Cite
|
Sign up to set email alerts
|

Functional involvement of P‐selectin and MAdCAM‐1 in the recruitment of α4β7‐integrin‐expressing monocyte‐like cells to the pregnant mouse uterus

Abstract: Leukocyte recruitment to the pregnant mouse uterus has been suggested to be associated with highly regulated expression of distinct patterns of vascular adhesion receptors. One of the most striking observations is the combined expression of mucosal addressin cell adhesion molecule-1 (MAdCAM-1) and P-selectin by maternal vessels of the vascular zone during the critical period of initial placenta development. The predominant cell population within these vessels is of the monocyte/macrophage lineage and expresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Among these, three common variants affecting P-selectin levels -2123G>C (rs1800807), -1969G>A (rs1800805) and N562D/C-2123G (rs6127) were reported (Barbaux et al, 2001), and were investigated here. Association of these variants with RPL was reported in some, but not in all studies (Fernekorn et al, 2004;Tometten et al, 2006). To the best of our knowledge, this is the first report that investigates the association of these polymorphisms in a North-African population.…”
Section: Introductionmentioning
confidence: 78%
“…Among these, three common variants affecting P-selectin levels -2123G>C (rs1800807), -1969G>A (rs1800805) and N562D/C-2123G (rs6127) were reported (Barbaux et al, 2001), and were investigated here. Association of these variants with RPL was reported in some, but not in all studies (Fernekorn et al, 2004;Tometten et al, 2006). To the best of our knowledge, this is the first report that investigates the association of these polymorphisms in a North-African population.…”
Section: Introductionmentioning
confidence: 78%
“…Blood lymphocytes express the MAdCAM-1 ligands ␣ 4 ␤ 7 integrin and CD62L, the former mediating homing to PP and the latter to peripheral lymph nodes (65). Because monocytes and neutrophils express CD62L and monocytes also express ␣ 4 ␤ 7 (37,54,55), we tested the role of MAdCAM-1 in monocyte and neutrophil recruitment to PP during oral Salmonella infection. However, normal recruitment of these cells was apparent when MAdCAM-1 was blocked.…”
Section: Discussionmentioning
confidence: 99%
“…5D) and the ␣ 4 integrin (37,54,55). CD62L and ␣ 4 partnered with ␤ 7 , in particular, are ligands for MAdCAM-1.…”
Section: Monocytes and Neutrophils Are Recruited To Pp Despite Blockimentioning
confidence: 99%
“…The cells can further be subdivided into two subsets: CD11b + α4β7 + cells (formerly called Mac-1 + β7 + cells), and CD11b -α4β7 + (formerly called Mac-1 − β7 + cells) (Fernekorn, 2004). Chronic administration of blocking antibodies against MAdCAM-1 in wild-type mice and P-selectin −/− mice, respectively, or experimental approaches with mice deficient in P-selectin or β7-integrin revealed that this unusual expression pattern has a critical impact on the recruitment of CD11b + α4β7 + cells, whereas the mechanisms underlying the extravasation of CD11b -α4β7 + leukocytes are still ill-defined ( Figure 2) (Fernekorn, 2004).…”
Section: Potential Mechanisms For Trafficking Of DC To the Decidualizmentioning
confidence: 99%